Legal Progressiveness for Heirs with Disabilities as a Form of Affirmative Action - Ananda Mardhotillah; Nur Rohim Yunus; Rosdiana Rosdiana (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study discusses the problem of the special inheritance section for heirs with disabilities as a form of legal progressiveness based on affirmative action. The distribution of inheritance based on needs provides a greater sense of justice because it is in line with the principle of proportionality. The purpose of this study is to determine and analyze the distribution of special inheritance for heirs with disabilities as a form of legal progressiveness based on affirmative action. The type of research used is normative juridical with a statute approach and a conceptual approach. The results of this study indicate that legal guarantees for heirs with disabilities are still very weak. However, the absence of the phrase heirs with disabilities and the inheritance section, in particular, indicates that the state does not provide a guarantee for the right to receive an inheritance and inherit. This study provides a solution in the form of regulating a special section for heirs with disabilities as a form of progressive Indonesian law based on affirmative action. The existence of special treatment for vulnerable groups is in line with the mandate of the constitution and the principle of justice of John Rawls in the theory of Justice as Fairness. The government, as a duty bearer, must continue to pay attention to heirs with disabilities by fully guaranteeing constitutional rights.Keywords: Disabled Heirs; Legal Progressiveness; Affirmative Action